Black carbon record of the wildfire history of western Sichuan Province in China over the last 12.8 ka - SUN, Weiwei; ZHANG, Enlou; SHEN, Ji; CHEN, Rong; LIU, Enfeng (Frontiers of earth science, 2016)
Wildfire is recognized as a critical Earth system process which affects the global carbon cycle, atmospheric chemistry, and ecosystem dynamics. Estimating the potential impact of future climate change on the incidence of fire requires an understanding of the long-term interactions of fire, climate, vegetation, and human activity. Accordingly, we analyzed the black carbon content and the pollen stratigraphy of sediments spanning the past 12.8 ka from Lake Muge Co, an alpine lake in western Sichuan Province, in order to determine the main factors influencing regional fire regimes. The results demonstrate that wildfires occurred frequently and intensively during the late deglaciation and the early Holocene when the regional vegetation was dominated by deciduous forests. Wildfire occurrence decreased significantly during the Holocene climatic optimum between 9.2 and 5.6 cal ka BP. Overall, the wildfire history of western Sichuan Province is similar to that of the Chinese Loess Plateau and of East Asia as a whole, suggesting that regional-scale fires depended mainly on changes in the intensity of the Asian summer monsoon. In addition, the fire regime of western Sichuan Province may have been influenced by the establishment of human settlement and agriculture in western Sichuan Province and the southeastern Tibetan Plateau after about 5.5 cal ka BP, and by an intensification of cereal cultivation coupled with population expansion in southwestern China during the last two millennia.